+0  
 
-2
43
1
avatar+199 

Find the following using the given functions . ( Simplify your answers completely.)

f ( x) = 6x3 − x2 + 4x + 5 and g ( x) = 9x3 − 1

 

  a. ( f  + g ) (x) = 

 

(b)

( f  + g ) (2) = 

 

(c)

( f  − g ) (x) = 

 

(d)

( f  − g ) (−3) =

 Apr 8, 2020
 #1
avatar+930 
0

a. (f+g)(x)= 6x^3-x^2+4x+5+9x^3-1= 15x^3-x^2+4x+4

b. (f+g)(2)= 15 * 2^3 - 2^2 + 4 * 2 + 4= 128

c. (f-g)(x)= 6x^3-x^2+4x+5-9x^3-1= -3x^3-x^2+4x+6

d. (f-g)(-3)= -3 * (-3)^3 - (-3)^2 + 4 * (-3) + 6= 66.

 

Hope it helps!

 Apr 8, 2020

24 Online Users

avatar
avatar
avatar
avatar